SISTEM INFORMASI ADMINISTRASI PEMBAYARAN BAGIAN ZAKAT, INFAQ, DAN SHADAQAH BERBASIS WEB DI SD IT AL-KHAIRAAT MENGGUNAKAN PHP DAN MYSQL - Sulastri, Yuliana; Rachamawati, Yuliana (Jurnal Script, 2015)
ABSTRACTAn educational institution requires a good administration to serve the needs of society. Administrative processing of the payment of zakat, infaq, shodaqoh (ZIS) students in SD Isam Al-Khairaat Yogyakarta is still conventional in which the recording of data is done in the book where the process can be time consuming, often mistaken and data storage is still a archives. To overcome these problems need to be made a computerized information system. The research method used by the writer is descriptive method with a case study in SD Isam Al-Khairaat Yogyakarta, collecting data by observation and interview. While the tools are used, among other things, the programming language PHP, MySQL database, the system development tools Use Case, Class diagrams, Sequence diagrams, Activity diagrams, and Relation table. The system built is expected to support the payment of zakat, infaq, shodaqoh (ZIS) including students new input system, input system ZIS payment that facilitate the search for the necessary student data and in terms of making monthly reports to be fast and timely. Keywords : Administration, Computerized, ZIS Payments, Information Systems.